The Upaya Guru Membangun Minat Belajar Siswa dengan Cara Berrmain; Teknik Sederhana Kurang Stress Belajar - Ahmad Yusuf; Shahibul Ihsan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
This study aims to describe the strategies employed by teachers to enhance students’ learning interest through the implementation of Game-Based Learning. Innovation in the learning process is essential to create a classroom environment that is enjoyable, interactive, and capable of increasing student engagement. Therefore, a game-based approach was applied as a learning strategy to provide students with a more attractive and meaningful learning experience. This study employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation involving teachers and students as research participants. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of Game-Based Learning significantly improved students’ interest in learning. This was evidenced by increased enthusiasm, active participation, and engagement during classroom activities. Furthermore, the method had a positive impact on students’ psychological well-being by reducing learning boredom and stress. The enjoyable, relaxed, and challenging learning experiences encouraged students to become more motivated in participating in educational activities. Therefore, Game-Based Learning can serve as an effective alternative strategy for enhancing students’ learning interest and improving the overall quality of the teaching and learning process in schools.